Effect of Personalized Instructor–Student E-mail and Text Messages on Online Students' Perceived Course Quality, Social Integration With Faculty, and Institutional Commitment. (August 2019) - Putulowski, Joe R.; Crosby, Robert G.
Social isolation among online college students may be a key contributor to the higher attrition rates reported by online universities relative to traditional institutions. This experiment investigated the effects of instructor–student communication on online students' self-reported social integration with faculty, institutional commitment, and perceived course quality. Participants were 242 students (26% men, 74% women) age 18 to 60 years ( M  = 30.00, SD  = 9.26) attending a midsized private Christian university in Southern California. Participants received varying frequencies (never, once, and weekly) and types (none, e-mail, and text) of personalized instructor–student messages. Students who received weekly messages rated their courses more highly after 4 weeks, but this effect later disappeared. There was no effect on social integration with faculty or institutional commitment. Results provide some support for consistent instructor–student communication but discourage a formulaic approach to combating student isolation and attrition.